Pengaruh Growth Opportunity, Intensitas Modal dan Ukuran Perusahaan terhadap Konservatisme Akuntansi pada Perusahaan Subsektor Transportasi yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2021 - Deviana Fadhila Aprilia Puspita; Ceacilia Srimindarti (Ekonomis: Journal of Economics and Business, 2023)
Accounting conservatism is a precautionary principle applied by companies in recording and reporting financial statements. This study aims to examine the effect of growth opportunity, capital intensity, and firm size on accounting conservatism in transportation sub-sector companies listed on the Indonesia Stock Exchange (IDX) in the period 2018–2021. The sampling method used is purposive sampling, with the amount of data processed as many as 94 companies from 152 companies. The data analysis technique used is multiple linear regression analysis. The results of this study show that growth opportunity and firm size have a significant positive effect on accounting conservatism. While capital intensity has no effect on accounting conservatism.